2006
DOI: 10.1037/0022-3514.91.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Going along versus going alone: When fundamental motives facilitate strategic (non)conformity.

Vladas Griskevicius,
Noah J. Goldstein,
Chad R. Mortensen
et al.

Abstract: Three experiments examined how 2 fundamental social motives-self-protection and mate attractioninfluenced conformity. A self-protective goal increased conformity for both men and women. In contrast, the effects of a romantic goal depended on sex, causing women to conform more to others' preferences while engendering nonconformity in men. Men motivated to attract a mate were particularly likely to nonconform when (a) nonconformity made them unique (but not merely a member of a small minority) and when (b) the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 314 publications
(158 citation statements)
references
References 87 publications
5
153
0
Order By: Relevance
“…There is some reason to suggest that the activation of social roles can lead to roleconsistent behavior. Previous research has found that the activation of a norm can lead to normconsistent behavior (Griskevicius et al, 2006), and thus we might expect the same for social roles.…”
Section: Social Role Explanations For Gender Differences In Conformitymentioning
confidence: 68%
See 4 more Smart Citations
“…There is some reason to suggest that the activation of social roles can lead to roleconsistent behavior. Previous research has found that the activation of a norm can lead to normconsistent behavior (Griskevicius et al, 2006), and thus we might expect the same for social roles.…”
Section: Social Role Explanations For Gender Differences In Conformitymentioning
confidence: 68%
“…Given the changes in social roles and the subtle changes in gender stereotypes, it seems plausible that gender differences in conformity may be waning. Furthermore, gender differences that have been reported recently in the literature (Collin et al, 1994;Ellis, Nel, & Van Rooyen, 1991;Larsen, 1990;Lee, 2006;Griskevicius et al, 2006;Reysen & Reysen, 2004) may have been caused by variables other than social role differences.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations